Coming to America : a history of immigration and ethnicity in American life - Daniels, Roger (New York, NY : HarperCollins, 1990)
A history of the waves of immigration to America from 1500 to the present.
Part I: Colonial America. Overseas migration from Europe ; English immigrants in America: Virginia, Maryland, and New England ; Slavery and immigrants from Africa ; Other Europeans in Colonial America ; Ethnicity and race in American life -- Part II: The Century of immigration (1820-1924). Pioneers of the century of immigration: Irish, Germans, and Scandinavians ; From the Mediterranean: Italians, Greeks, Arabs, and Armenians ; Eastern Europeans: Poles, Jews, and Hungarians ; Minorities from other regions: Chinese, Japanese, and French Canadians ; The triumph of nativism -- Part III: Modern times. Migration in prosperity, depression, and war, 1921-1945 ; From the New World: Mexicans and Puerto Ricans ; Changing the Rules: Immigration Law, 1948-1980 ; The New Asian immigrants ; Caribbeans, Central Americans, and Soviet Jews ; The 1980's and beyond.
Includes bibliographical references (pages 423-431) and index.
Keywords: Ethnology -- United States -- History; Immigrants -- United States -- History; Emigration and Immigration -- history; Anthropology, Cultural